Reducing occupational sedentary time: A systematic review and meta-analysis of evidence on activity-permissive workstations - Neuhaus, M.; Eakin, E.; Straker, Leon; Owen, N.; Dunstan, D.; Reid, N.; Healy, Genevieve (Wiley-Blackwell Publishing Ltd., 2014)
Excessive sedentary time is detrimentally linked to obesity, type 2 diabetes, cardiovascular disease and premature mortality. Studies have been investigating the use of activity-permissive workstations to reduce sedentary time in office workers, a highly sedentary target group. This review systematically summarizes the evidence for activity-permissive workstations on sedentary time, health-risk biomarkers, work performance and feasibility indicators in office workplaces. In July 2013, a literature search identified 38 relevant peer-reviewed publications. Key findings were independently extracted by two researchers. The average intervention effect on sedentary time was calculated via meta-analysis. In total, 984 participants across 19 field-based trials and 19 laboratory investigations were included, with sample sizes ranging from n = 2 to 66 per study. Sedentary time, health-risk biomarkers and work performance indicators were reported in 13, 23 and 23 studies, respectively. The pooled effect size from the meta-analysis was -77 min of sedentary time/8-h workday (95% confidence interval = -120, -35 min). Non-significant changes were reported for most health- and work related outcomes. Studies with acceptability measures reported predominantly positive feedback. Findings suggest that activity-permissive workstations can be effective to reduce occupational sedentary time, without compromising work performance. Larger and longer-term randomized-controlled trials are needed to understand the sustainability of the sedentary time reductions and their longer term impacts on health- and work-related outcomes.